1999
DOI: 10.1017/s1355838299990313
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Rrp5p in the synthesis of yeast 18S and 5.8S rRNA can be functionally and physically separated

Abstract: The yeast nucleolar protein Rrp5p is the only known trans-acting factor that is essential for the synthesis of both 18S rRNA and the major, short form of 5.8S (5.8Ss) rRNA, which were thought to be produced in two independent sets of pre-rRNA processing reactions. To identify domains within Rrp5p required for either processing pathway, we have analyzed a set of eight deletion mutants that together cover the entire RRP5 sequence. Surprisingly, only one of the deletions is lethal, indicating that regions encompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
87
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 35 publications
10
87
0
1
Order By: Relevance
“…Depletion of L3 elicits the earliest block in 27S pre-rRNA processing: cleavage at the A 3 site in 27SA 2 pre-rRNA (Supplemental Fig. 2A,C), similar to that seen when depleting the N-terminal half of Rrp5 (Eppens et al 1999) that cross-links immediately downstream from the A 3 site (Lebaron et al 2013). Thus, while cleavage at the A 2 site to create the 59 end of 27S prerRNA occurs cotranscriptionally (Kos and Tollervey 2010), subsequent processing at the A 3 site of 27SA 2 pre-rRNA appears to occur post-transcriptionally, after proper formation of the 39 end of 27S pre-rRNA.…”
Section: Discussionmentioning
confidence: 62%
“…Depletion of L3 elicits the earliest block in 27S pre-rRNA processing: cleavage at the A 3 site in 27SA 2 pre-rRNA (Supplemental Fig. 2A,C), similar to that seen when depleting the N-terminal half of Rrp5 (Eppens et al 1999) that cross-links immediately downstream from the A 3 site (Lebaron et al 2013). Thus, while cleavage at the A 2 site to create the 59 end of 27S prerRNA occurs cotranscriptionally (Kos and Tollervey 2010), subsequent processing at the A 3 site of 27SA 2 pre-rRNA appears to occur post-transcriptionally, after proper formation of the 39 end of 27S pre-rRNA.…”
Section: Discussionmentioning
confidence: 62%
“…of both the 18S and the 25S/5.8S rRNAs (Venema and Tollervey 1996;Torchet et al 1998;Eppens et al 1999). Here, we report that Rrp12p is required for the late maturation of the 18S and 5.8S rRNA.…”
Section: Discussionmentioning
confidence: 63%
“…Somewhat similar pre-rRNA processing phenotypes have been observed in cells depleted of the essential protein Rrp7p (Baudin-Baillieu et al+, 1997), in a strain lacking the snR10 H/ACA snoRNA (Tollervey, 1987), or in cells expressing a N-terminal and a C-terminal domain of the Rrp5p protein separately (Venema & Tollervey, 1996, Torchet et al+, 1998Eppens et al+, 1999)+ Strikingly, the 21S pre-rRNA accumulates in all these cases+ In Rrp7p-depleted cells as well as in the snR10⌬ strain, however, the 23S aberrant pre-rRNA can be observed in addition to the 21S species, showing that cleavages at sites A1 and A0 are more affected than in the absence of Rrp8p+ In the strain expressing the socalled "bipartite" rrp5 allele (Torchet et al+, 1998), only 21S and no 23S or 20S pre-rRNAs are observed, yet mature 18S rRNA gets produced+ This shows that the 21S pre-rRNA can be a direct precursor to 18S rRNA and lends support to our assumption that in rrp8⌬ cells, most mature 18S rRNA molecules are produced directly from 21S+…”
Section: Discussionmentioning
confidence: 63%